Molecular identification of potential ciprofloxacin degrading bacteria and determination of its possible breakdown intermediates in rivers, Eastern Cape - Ngcauzele, Zenande Rose (Rhodes University, Faculty of Pharmacy, Pharmacy)
Thesis embargoed. To be released early 2026.
Keywords: Uncatalogued